2004
DOI: 10.1080/00365520410003209
|View full text |Cite
|
Sign up to set email alerts
|

Capsule endoscopy: role of bowel preparation in successful visualization

Abstract: Bowel preparation with sodium phosphate before capsule endoscopy offers better visualization than overnight fasting alone and induces fewer disturbances by intraluminal turbid fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
7

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 10 publications
2
52
0
7
Order By: Relevance
“…(Viazis N et al, 2004;Mylonaki M et al, 2003) when compared to clear liquids alone. (Niv Y et al, 2004;Cave D et al, 2004;Ning D et al, 2005) However, a number of recent studies and meta-analyses concluded that bowel preparation is not necessary, as it does not improve the image quality or diagnostic rate of CE investigations. This conclusion is also supported by the latest consensus reports (de Franchis R et al, 2005) as well as by official recommendations given by several major capsuleproducing companies.…”
Section: Bowel Preparationmentioning
confidence: 99%
“…(Viazis N et al, 2004;Mylonaki M et al, 2003) when compared to clear liquids alone. (Niv Y et al, 2004;Cave D et al, 2004;Ning D et al, 2005) However, a number of recent studies and meta-analyses concluded that bowel preparation is not necessary, as it does not improve the image quality or diagnostic rate of CE investigations. This conclusion is also supported by the latest consensus reports (de Franchis R et al, 2005) as well as by official recommendations given by several major capsuleproducing companies.…”
Section: Bowel Preparationmentioning
confidence: 99%
“…Efforts are being made to control the transit of the capsule and to optimize cleansing of the small bowel (20,21). The consensus at this point is that the use of bowel preparations and pro-kinetics may reduce the number of failed examinations, but the optimal solution has yet to be found (22).…”
Section: The Proceduresmentioning
confidence: 99%
“…At present, although all published papers strongly underlined that small bowel cleanliness is a key point to ensure a complete and accurate examination, and several papers aimed at evaluating factors (dietary restrictions and/or laxatives and/or prokinetic and/or postural tricks) potentially affecting small bowel cleanliness [12,14,16,17,[89][90][91][92][93] have been published, there are still no recommendations about small bowel preparation for capsule endoscopy.…”
Section: Risks and Limitationsmentioning
confidence: 99%